Pelatihan Desain Media Pembelajaran Berbasis Canva di MGMP Informatika SMA Kabupaten Semarang - Vici Tiara Anjarsari; Afrizal Nurkhiri; Muh Kholid Rizky Sapawi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
After the COVID-19 pandemic, students' learning patterns have changed significantly, with an increasing reliance on technology and interactive media. This shift requires teachers to be more adaptive in delivering engaging and effective learning materials. However, not all teachers have the necessary skills to design technology-based learning media. To address this challenge, the MGMP Informatika SMA of Semarang Regency organized a Canva-Based Learning Media Design Training at SMA Negeri 1 Bringin. This training aimed to equip teachers with the skills to design learning media using Canva, a user-friendly design platform. The training was conducted in several stages: preparation, implementation, evaluation, and documentation. The evaluation results showed that before the training, 72% of participants struggled with designing learning media, and 60% were unfamiliar with Canva. After the training, 100% of participants were interested in using Canva, 84% felt more confident in utilizing it, and 92% expressed satisfaction with the training.